Software for the National Health Insurance Scheme: Pharmacy Management - Yeboah, Paul Kwame (2011)
A Thesis submitted to the School Of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science (M.Sc) Industrial Mathematics,